Pollen grains morphology characters and the chromosomal number of Some Chenopodiaceae plants - Haider Radhi Malih (مجلة علوم ذي قار, 2019)
The pollen morphology characters and chromosome number of Arthrocnemum glaucum Del., Halocnemum strobiloceum (Pall.) M. Bieb.  and Salicornia europaea L. (Salicornieae: Chenopodiaceae) plants were studied. The pollen grains were characterized by isopolate, spheroidal, polyporate, circular pore and verrucate ornamentation, while the pollen diameter, pore number and C/D ratio have been shown to give a good taxonomic value, the results illustrated divided the species in tow groups. The first group includes A. glaucum   and S. europaea with small size of pollen grains, while isolated H. strobiloceum in other group.The chromosomal numbers were count in all species, which divided into two groups, the first was includes the H. strobiloceum and S. europaea species with (n= 18) chromosome, while A. glaucum was posited on the other group with (n= 9) chromosome.